Metastatic Extramammary Paget’s Disease of Scrotum Responds Completely to Single Agent Trastuzumab in a Hemodialysis Patient: Case Report, Molecular Profiling and Brief Review of the Literature - Peter Barth; Essel Dulaimi Al-Saleem; Kristin W. Edwards; Sherri Z. Millis; Yu-Ning Wong; Daniel M. Geynisman (Case Reports in Oncological Medicine)
Extramammary Paget’s disease (EMPD) is a rare cancer. Although EMPD is usually noninvasive and treated with local therapy, once metastatic the prognosis of EMPD is poor and treatment options are limited. We report a case of a complete response to single agent trastuzumab in a hemodialysis patient with metastatic Her2/neu overexpressed EMPD of the scrotum. Molecular profiling of his case as well as 12 other EMPD and 8 mammary Paget disease (MPD) cases was completed and revealed multiple biomarker aberrations. Overexpression of Her2 was frequently noted (30%–40%) in both EMPD and MPD patients and when present can be effectively treated with Her2 targeted agents. Trastuzumab therapy can be safely utilized in a hemodialysis patient. In addition, multiple protein overexpression and loss were seen in EMPD including PD-1, PD-L1, PTEN, and AR as well as PIK3CA mutation. These findings may lead to possible therapeutic interventions targeting these pathways in a disease with few effective treatment options.